ANALISIS PENGENDALIAN BAHAN BAKU TEPUNG TAPIOKA MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PT. BUDI STARCH & SWEETENER, TBK - Tauva, Kelvin Ardana; Chamidah, Siti; Pristi A, Eka Destriyanto (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The purpose of this study is to find the optimal raw material inventory of a company if it is calculated using the EOQ method. (case study at Pt. Budi Strach & Sweetener, Tbk). The data used in this study were taken from the company's books and from interviews with the HRD personnel of Pt. Budi Strach & Sweetener, Tbk in 2021. The data used in this study are: purchase data, usage data, purchase frequency, raw material inventory data, cassava raw material ordering data, raw material storage cost data. The analysis was carried out using the EOQ formula, safety stock, reorder point, total cost, purchase frequency. The problem in this research is Pt. Budi Strach & Sweetener, Tbk in its production experience a shortage of raw materials every year because the supply of raw materials in the field is uncertain, so here the author tries to apply the Economic Order Quantity (EOQ) method to minimize various aspects in the procurement of raw material supplies. The results of this study indicate that: Control of raw materials Economic Order Quantity (EOQ) method is considered more efficient and optimal, it is proven that there is a decrease in inventory costs of Rp. 3,219,502. Judging from the company's policy, the optimal purchase of raw materials according to company policy is 1,353,378 Kg with a purchase frequency of 24 times, while according to the policy of the EOQ Method, the purchase of raw materials is 1,813,140 Kg with a purchase frequency of 18 times a year. Total Safety Stock according to EOQ policy is 15,954 Kg. Re-Order Point (Re-Order Point) according to the policy of the EOQ Method is 376,854,444 Kg. The analysis shows that the use of the EOQ method in controlling cassava raw materials at Pt. Budi Strach & Sweetener, Tbk is considered effective and efficient